1998
DOI: 10.1074/jbc.273.2.829
|View full text |Cite
|
Sign up to set email alerts
|

Prodynorphin Processing by Proprotein Convertase 2

Abstract: Endoproteolytic processing of the 26-kDa protein precursor prodynorphin (proDyn) at paired and single basic residues is most likely carried out by the proprotein convertases (PCs); however, the role of PCs at single basic residues is unclear. In previous studies we showed that limited proDyn processing by PC1/PC3 at both paired and single basic residues resulted in the formation of 8- and 10-kDa intermediates. Because PC2 is colocalized with proDyn, we examined the potential role of this convertase in cleaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 51 publications
(44 reference statements)
2
53
0
Order By: Relevance
“…A number of studies (both in vitro as well as in vivo) implicate PC1 and PC2 in ProDyn processing (12)(13)(14). Studies using mice lacking PC2 activity (PC2 K/O) show a complete lack of Dyn A-8 and substantially reduced levels of Dyn A-17 and Dyn B-13 (13,14).…”
mentioning
confidence: 99%
“…A number of studies (both in vitro as well as in vivo) implicate PC1 and PC2 in ProDyn processing (12)(13)(14). Studies using mice lacking PC2 activity (PC2 K/O) show a complete lack of Dyn A-8 and substantially reduced levels of Dyn A-17 and Dyn B-13 (13,14).…”
mentioning
confidence: 99%
“…These results suggest that although PC1 is able to process prodynorphin at monobasic sites, the efficiency of processing at this site is substantially lower than the processing at dibasic sites. Recent studies have shown that purified PC2 is able to process prodynorphin efficiently, generating dynorphin A-8 and dynorphin B-13 (Berman et al, 1997;Day et al, 1998), supporting a role for PC2 in the processing of prodynorphin at monobasic sites.…”
Section: Discussionmentioning
confidence: 99%
“…The RIA against Dyn A-(1-8) has been extensively characterized (4,24). Briefly, the Dyn A-(1-8) antibody is C-terminally targeted and does not cross-react with Dyn A-(1-17) or larger forms of pro-Dyn-derived peptides.…”
Section: Methodsmentioning
confidence: 99%
“…7A). The formation of Dyn A-(1-8) is specifically due to the cleavage of its precursor Dyn A-(1-17) by SPC2 (24). The production of the Dyn A-(1-8) is an exclusive character of the ␀TC-3 cells (4), and as a consequence, inhibition of the enzyme can be monitored by analysis of this peptide in crude protein extracts by RIA.…”
Section: Identification Of Potential Targetmentioning
confidence: 99%